Justification of Urgent Brain CT Examinations at Medium Size Hospital, Jerusalem (Atlas Journal of Biology, 2019)
We studied requested urgent Brain CT Scan procedures justification. In addition, we addressed referrer’s (physician’s) awareness of radiation risks. In doing so, we considered two aspects to the issue. First, we reviewed the records of the requested urgent CT scan procedures for a sample of 339 patients at Al-Maqassed Hospital, a major hospital in Palestine. Secondly, we surveyed a sample of forty-two referrer’s from the same hospital to test their awareness of radiation risks. Our study shows that out of the 339 urgent brain CT requests, 69.6% were justified requests and 30.4% were unjustified. On the other hand, our survey on referrers shows that 42% of respondents knew the effective dose of a brain CT scan, 24% of respondents knew the radiation risks and 14% of respondents knew about radiation protection. Although the study is limited, yet it shows the need to reduce the number of brain CT examinations and the need to improve their justification. Consequently, the need for regular education and guideline implementation at least in this country is of paramount importance